Research and Prospects of Airtightness of Biological Laboratory Enclosures: Influencing Factors and Evaluation Methods - Geqing Peng; Xiaoshuang Shi; Ruihan Hu; Xiaoli Wang; Jinsheng Zhan (Buildings, 2025)
The airtightness of enclosures in biological laboratories is paramount for effective isolation between internal and external environments, ensuring containment of hazardous pathogens and mitigating accidental release risks. Consequently, studying and enhancing the airtightness of these enclosures significantly contributes to maintaining laboratory safety, safeguarding personnel health, and preventing disease. This paper examines the critical role of the enclosure structure in biological laboratories and how airtightness impacts the laboratory environment. It analyzes the current state of research on the airtightness of high-level biological laboratory enclosures, drawing on domestic and international sources. This includes exploring issues and challenges related to material properties, process methods, and evaluation methods for the airtightness of concrete structural materials as well as steel structures. The paper also studies the airtightness of enclosure structures of biological laboratories, highlighting the shortcomings in this important field of research and its future prospects.